IMPACT OF PRODUCTS AND SERVICES ON BUY DECISIONS (Studi D’royal Mart Di Batuphat Timur, Muara Satu Lhokseumawe) - Sari maharani Sitorus; Nanda Ameliany; Nursakinah Ritonga; Teuku Zulkarnaen; Lisa Iryani; Sufi, Sufi (Jurnal Intelek Insan Cendikia, 2024)
This study uses a quantitative approach which aims to determine the completeness of products and services that have a positive and significant influence on purchasing decisions. The population in this study were all visitors to the D'royal Mart Store in East Batuphat, Muara Satu Lhokseumawe and determining the sample using a Likert scale with the accidental samling technique method. The data obtained was analyzed using multiple regression analysis. The results showed that using the t-test, the t-value was 4.350 with a p-value (0.000 <0.05), which means that hypothesis 1 which states that there is an effect of product completeness on purchasing decisions can be accepted. The t-test results obtained a t-count value of 2.905 with a p-value (0.000 <0.05) which means that hypothesis 2 which states that there is an effect of service on purchasing decisions can be accepted. The simultaneous test results obtained with a p-value (0.000 <0.05) which means that hypothesis 3 there is an influence between product completeness and service on purchasing decisions at D'royal Mart Batuphat Timur, Muara Satu Lhokseumawe simultaneously can be accepted. In this study, the results of the R squaer analysis obtained 0.611, which means that the percentage of the influence of product completeness and service on purchasing decisions is 61.1% and the remaining 38.9% is influenced by other variables not examined.